Transition-Metal-Catalyzed Direct Arylation of Ammonia - Song, Geyang; Dong, Jianyang; Song, Jiameng; Li, Gang; Xue, Dong (Synthesis, 2024)
In the past few decades, transition-metal-catalyzed direct amination of aryl halides with ammonia has attracted significant attention from chemists because of its broad substrate scope, good functional group compatibility, and high reaction selectivity. Herein, recent examples of transition-metal-catalyzed syntheses of aniline derivatives starting from aryl halides are reviewed.1 Introduction2 Heat-Driven Transition-Metal-Catalyzed Amination of Aryl Electrophiles2.1 Palladium-Catalyzed Amination2.2 Copper-Catalyzed Amination2.3 Nickel-Catalyzed Amination3 Light-Driven Transition-Metal-Catalyzed Amination of Aryl Electrophiles4 Conclusion and Outlook
Keywords: transition-metals; anilines; aryl electrophiles; amination; cross-coupling; photocatalysis; thermal-driven; catalysis